The Cultural-Reflexive Function And Frame Semantics Of Proverbs: A Journey Through Uzbek And English Mindsets - Tolibova, Nodira Nosirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article explores proverbs not merely as linguistic artifacts, but as cognitive "mirrors" that reflect the collective soul of a nation. By applying Frame Semantics, we investigate how Uzbek and English speakers organize their cultural experiences into mental structures. The study highlights the cultural-reflexive function of proverbs—how they allow a society to look at itself, judge its members, and pass down survival strategies. Through a comparative analysis, we reveal how the "Hospitality" frame in Uzbek and the "Independence" frame in English create distinct linguistic realities.